2003
DOI: 10.1038/sj.bdj.4810032
|View full text |Cite
|
Sign up to set email alerts
|

Does oral contraceptive use affect the incidence of complications after extraction of a mandibular third molar?

Abstract: Objective This study investigated whether oral contraceptive use affects the incidence of complications (pain, trismus, dry socket) in women undergoing removal of impacted mandibular third molars. Patients and method Two hundred and sixty seven women, aged 17 -45 years, underwent removal of an impacted mandibular third molar. Eighty seven of the women were regular users of oral contraceptives. All patients were evaluated for postoperative pain, trismus and dry socket (localized alveolar osteitis). Results Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 16 publications
5
36
0
4
Order By: Relevance
“…These include the patient's sex, 7 the use of oral contraceptives, 8 smoking, 9 patient age, 10 difficulty of the extraction, 11 surgeon's experience, 12 preoperative infection, 13 and the menstrual cycle. 14 and 15 Signs and symptoms of AO often develop within 1-3 days following surgery.…”
mentioning
confidence: 99%
“…These include the patient's sex, 7 the use of oral contraceptives, 8 smoking, 9 patient age, 10 difficulty of the extraction, 11 surgeon's experience, 12 preoperative infection, 13 and the menstrual cycle. 14 and 15 Signs and symptoms of AO often develop within 1-3 days following surgery.…”
mentioning
confidence: 99%
“…Patient's brief history and examination details were recorded in a specially designed perform for this purpose. Patients with thyroid disorders, pregnant ladies, women on oral contraceptives [9] uncontrolled diabetics, uncontrolled hypertensive, cardiac patients and patients with chronic renal disease were not included in the study because alteration in post op drug regimen can cause bias. Patients included in the study were advised not to smoke (if they were smokers) at least for three days before surgery to one week after surgery as López-Carriches C et al, [10] found that smoking increases chances of trismus.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies 9,26 have also shown that younger people have a higher incidence of dry socket following extraction. Factors such as oral contraceptive use have been shown recently to favour the appearance of dry socket, 27 and this may be explained by their fibrinolytic activity. However, other studies have found no increased incidence of dry socket with oral contraceptive use.…”
Section: Too Small a Sample Size Was Used In Our Studymentioning
confidence: 99%